Studi Heterotopia pada Ruang Sembahyang di Hunian Masyarakat Tionghoa Surabaya - Sumingto, Anastasya; Tulistyantoro, Lintu; Lumintan, William Vijadhammo (Waca Cipta Ruang, 2023)
Heterotopia is a phenomenon that occurs in the functioning of space and refers to the unreal space present in a real room. Where the incident can be interpreted, there are other functions of the room in the context of different spatial characters even though they do not negate each other. This event usually occurs in the living room of the Chinese community residence. This phenomenon can happen because the living room, which in fact is located as a real space, can function in addition to being a place to receive guests (profane), but at certain conditions in the form of time and human behavior can also affect and change the function of the space into a place of prayer to accommodate their spirituality (sacred) activities. The purpose of this study is to be able to review the specifics of the application of the principle of heterotopia space and the supporting factors that influence it. The research method used is a qualitative approach with a descriptive analysis method in the form of depictions accompanied by analysis supported by taking photos, literature data, and interviews. Thus the principle of heterotopia that occurs in the living room of the Chinese community is caused by the influence of Chinese culture, the time & activities it carries out, as well as the formation of an atmosphere of spiritual dimension which is also supported by elements of furniture accompanied by prayer equipment in the form of incense as the main supporting factor so that the living room can change its function to be more sacred and private.